The Influence of the "Magna Carta" on British Constitution - Han, Zixin (Transactions on Social Science, Education and Humanities Research, 2023)
The constitutions of most countries in the world are established by specific institutions at particular historical moments after bourgeois revolutions or reforms, and therefore usually take the form of complete written codices. However, the British constitution is different, having been gradually formed over several centuries through continuous amendments and accumulation. This paper, based on previous literature and charter ordinances, delves into the influence of the "Magna Carta" on the British constitution, covering aspects such as limiting the power of the monarchy, the supremacy of law, human rights protection, and the parliamentary system. As an important milestone in history, the "Magna Carta" has made significant contributions to the shaping and evolution of the British constitutional system, defining the basic features of the British political system.